Helping Students Make Sense of New Material Through the “I Notice I Wonder” Method - Hotimah, Iis Husnul; Supriatna, Encep (Universitas Pendidikan Indonesia Kampus Serang, 2024)
When a student becomes an active doer during the learning process, the advantage of their mindset can be realized. The understanding process started when the teacher created a class atmosphere that attracted student’s curiosity. By throwing questions such as